The effect of metabolic acidosis on the synthesis and turnover of rat renal phosphate-dependent glutaminase. - Tong, J (1986)
Regulation of the mitochondrial phosphate-dependent glutaminase activity is an essential component in the control of renal ammoniagenesis. Alterations in acid-base balance significantly affect the amount of the glutaminase that is present in rat kidney, but not in brain or small intestine. The relative rates of glutaminase synthesis were determined by comparing the amount of [35S]methionine incorporated into specific immunoprecipitates with that incorporated into total protein. In a normal animal, the rate of glutaminase synthesis constitutes 0.04% of the total protein synthesis. After 7 days of metabolic acidosis, the renal glutaminase activity is increased to a value that is 5-fold greater than normal. During onset of acidosis, the relative rate of synthesis increases more rapidly than the appearance of increased glutaminase activity. The increased rate of synthesis reaches a plateau within 5 days at a value that is 5.3-fold greater than normal. Recovery from chronic acidosis causes a rapid decrease in the relative rate of glutaminase synthesis, but a gradual decrease in glutaminase activity. The former returns to normal within 2 days, whereas the latter requires 11 days. The apparent half-time for glutaminase degradation was found to be 5.1 days and 4.7 days for normal and acidotic rats respectively. These results indicate that the increase in renal glutaminase activity associated with metabolic acidosis is due primarily to an increase in its rate of synthesis. From the decrease in activity that occurs upon recovery from acidosis, the true half-life for the glutaminase was estimated to be 3 days.